A novel indole-based conjugated microporous polymer for highly effective removal of heavy metals from aqueous solution via double cation–π interactions. Issue 69 (6th December 2019) - Wang, Qiang; Li, Rui; Ouyang, Xiao; Wang, Guojun
Abstract : A novel indole-based conjugated microporous polymer (PTIA) with three coplanar indole units, designed and synthesized by an oxidative coupling reaction, was utilized as a platform for removing heavy metals. Abstract : A novel indole-based conjugated microporous polymer (PTIA) with three coplanar indole units, designed and synthesized by an oxidative coupling reaction, was utilized as a platform for removing heavy metals. Owing to the conjugation of the three coplanar indoles, the highly electron-rich large π planes can simultaneously attract six heavy metal atoms via double cation–π interactions, endowing this microporous material with remarkable heavy metal adsorption capacity and efficiency.